2021
DOI: 10.1128/mbio.01947-20
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Regulates Granuloma Formation and Macrophage Activation during Mycobacterium avium Infection via Mediating Nramp1 and HO-1 Expressions

Abstract: Nrf2 is a redox-sensitive transcription factor that is thought to be important in protection against intracellular pathogens. To determine the protective role of Nrf2 in the host defense against Mycobacterium avium complex (MAC), both wild-type and Nrf2-deficient mice were intranasally infected with MAC bacteria. Nrf2-deficient mice were highly susceptible to MAC bacteria compared with wild-type mice. There were no significant changes in the levels of oxidative stress and Th1 cytokine production between genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…By contrast, an oxidative environment has been shown to favour Mabs growth in macrophages (66,67). Moreover, activation of Nrf2 reduces the bacterial burden both in vitro and in vivo (47,48,50,68).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, an oxidative environment has been shown to favour Mabs growth in macrophages (66,67). Moreover, activation of Nrf2 reduces the bacterial burden both in vitro and in vivo (47,48,50,68).…”
Section: Discussionmentioning
confidence: 99%
“…The Mycobacterium avium -intracellulare complex strain is a clinical isolate from patients at Emory University Hospital and was kindly provided by Dr. Eileen M Burd. The strain was cultured in Middlebrook 7H9 broth (BD-Difco, Franklin Lakes, NJ, USA), as previously described [ 63 ]. Colony-forming units (CFUs) were determined on Middlebrook 7H11agar plates (BD-Difco).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Nakajima et al reported that NRF2-deficient mice were highly susceptible to M. avium bacteria compared to wild-type mice [ 81 ]. Surprisingly, NRF2 did not affect the level of oxidative stress or Th1 cytokine production in this M. avium -infection model.…”
Section: The Role Of Nrf2 In Ntm Infectionmentioning
confidence: 99%
“…Taken together, higher susceptibility of the elderly to pulmonary NTM infection is partly caused by attenuated HO-1 responses, subsequent upregulation of SOCS3 , and inhibition of Bcl2 , leading to programmed cell death of macrophages and sustained infection. Since HO-1 is induced under the influence of NRF2 in young mice in response to NTM infection [ 81 ], it is likely that increased susceptibility to mycobacterial infection in the elderly is related to the decline of NRF2 functions with advancing age.…”
Section: Aging and Nrf2 In Mycobacterial Infectionmentioning
confidence: 99%
See 1 more Smart Citation